The Impact of Postal Voting on Participation: Evidence for Switzerland - Simon Luechinger; Myra Rosinger; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2006)
Many countries are forging ahead with convenient balloting methods, in particular electronic and postal voting, in order to re-engage voters. In this paper, we test whether the cost reductions with postal voting increase turnout. The empirical analysis is based on a newly collected data set on the introduction of postal voting in Swiss cantons. We take advantage of the unique fact that voting by mail was introduced at different times across cantons. This allows identifying the impact of postal voting on turnout, independent of time, issue and canton specific effects. The estimated average effect on turnout is roughly 4.1 percentage points for an average turnout of 43 percent between 1970 and 2005.
Keywords: D72; 330; postal voting; voting costs; voting participation; turnout; Wahlverhalten; Wahlsystem; Schätzung; Schweiz